CHARACTERIZE THE FUNCTIONING CONDITIONS OF THE PUBLIC AND PRIVATE ELDERLY CARE INSTITUTIONS OF THE COUNTY OF RIO DE JANEIRO. (Fiep Bulletin - online, 2014)
The quick aging of the Brazilian population observed in the last decades requires new assistance and health services net destinated to the elderly. The study had as a goal characterizing the functioning conditions of the elderly care institutions in Rio de Janeiro in the neighborhoods of Bangu, Campo Grande and Campinho. The approach was done through an observational, descriptive study thoughout a semi-structured quiz to obtain interesting data to the study, including infrastructure, provided services and offered activities. We concluded that it is necessary attention and qualification of the human resources to the treatment of the elderly, specifically, followed by the inspection of the representative body.
Keywords: elderly care institution; elderly; inspection